2019
DOI: 10.18632/aging.102353
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy of ticagrelor in acute ST-segment elevation myocardial infarction patients undergoing an emergency percutaneous coronary intervention

Abstract: In total, 97 acute ST-segment elevation myocardial infarction (STEMI) patients who received an emergency percutaneous coronary intervention (PCI) were enrolled and divided into a ticagrelor group and a clopidogrel group. Thrombolysis in myocardial infarction (TIMI) blood flow and the corrected TIMI frame count (CTFC) were used to assess the blood perfusion of culprit vessels. Thromboelastography (TEG) was used to evaluate the antiplatelet effect of drugs. The results showed that the incidence of TIMI grade III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“… 9 Currently, the guidelines have pointed out that emergency PCI was the preferred method to open the diseased vessels in STEMI patients and to realize revascularization. 10 A previous study have demonstrated that the peak values of CK and CK-MB were positively correlated with the infarct size of STEMI patients 11 , which was consistent with our results, that is, higher peak values of CK and CK-MB were associated with larger the infarct size. It has been suggested the gold standard for successful reperfusion was to reach TIMI3 blood flow in the infarction-related vessels.…”
Section: Discussionsupporting
confidence: 92%
“… 9 Currently, the guidelines have pointed out that emergency PCI was the preferred method to open the diseased vessels in STEMI patients and to realize revascularization. 10 A previous study have demonstrated that the peak values of CK and CK-MB were positively correlated with the infarct size of STEMI patients 11 , which was consistent with our results, that is, higher peak values of CK and CK-MB were associated with larger the infarct size. It has been suggested the gold standard for successful reperfusion was to reach TIMI3 blood flow in the infarction-related vessels.…”
Section: Discussionsupporting
confidence: 92%
“…Five publications were eliminated (one article investigated the ACS population but lacked detailed data on STEMI patients; four trials did not focus on STEMI patients; in one trial, indicators of microcirculation did not appear in other studies). We finally included seven RCTs (16)(17)(18)(19)(20)(21)(22) in the present analysis.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…PPCI is the standard and preferred treatment in STEMI with acceptable efficacy compared to other treatment options [ 15 ]. In a clinical trial conducted in 2019 by Cao et al [ 16 ], the short-term outcomes of the STEMI patient candidates for PPCI who received ticagrelor or clopidogrel were compared. There was no significant difference between the two groups regarding TIMI flow grade zero, grade I, and grade II; However, grade III TIMI flow was more frequent in the ticagrelor group than in the clopidogrel group ( p =0.016).…”
Section: Discussionmentioning
confidence: 99%